2002
DOI: 10.1007/s11661-002-0246-7
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial dislocation networks strengthening a fourth-generation single-crystal TMS-138 superalloy

Abstract: The ␥ /␥ Ј interfacial dislocation networks in several creep-ruptured superalloys were analyzed. It was found that the morphologies of dislocation networks differ slightly from each other in these alloys. The fourth-generation superalloy has finer dislocation networks and keeps a relatively stable state. Comparatively, the interfacial dislocations in the third-generation superalloy show obvious curved features associated with possible climb or slip. These interfacial dislocation characteristics can be correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(88 citation statements)
references
References 11 publications
(2 reference statements)
2
85
0
1
Order By: Relevance
“…As will be shown, Ru was determined to be a critical element to the success of the alloy development program as it could be added to achieve both improved microstructural stability and increased high temperature creep strength. Subsequent alloy development efforts by others [4][5][6] have led to similar conclusions on the usefulness of Ru in 4 th generation single crystal superalloys.…”
Section: Introductionmentioning
confidence: 78%
“…As will be shown, Ru was determined to be a critical element to the success of the alloy development program as it could be added to achieve both improved microstructural stability and increased high temperature creep strength. Subsequent alloy development efforts by others [4][5][6] have led to similar conclusions on the usefulness of Ru in 4 th generation single crystal superalloys.…”
Section: Introductionmentioning
confidence: 78%
“…Since introduction in the late 1970's, single crystal (SX) alloy development has generally focused on increased temperature capability, and major improvements in alloy performance have been associated with the introduction of new alloying elements, including rhenium (Re) and ruthenium (Ru) [1,2]. Rhenium has been widely used in advanced single crystal superalloys for turbine blade, vane and seal segments due to its potent effect in slowing diffusion and hence creep deformation and fatigue crack initiation under high temperature operating conditions [3].…”
Section: Introductionmentioning
confidence: 99%
“…The minimum creep rate decreases with the decrease of dislocation spacing in the γ /γ interface at each temperature. Zhang et al [5] described the relationship between the interfacial dislocation spacing, minimum creep rate and γ /γ lattice misfit at high temperature under low stress creep deformation. In the present study, the interfacial dislocation spacing at the corresponding minimum creep rate at 1000 • C and at 1050 • C were different.…”
Section: Resultsmentioning
confidence: 99%
“…In general, more refractory elements such as rhenium improve the creep resistance of the materials for advanced turbine blade [1][2][3][4]. It has also been reported that the γ /γ rafting behaviour is effective for creep resistance in case of the single crystal (SX) superalloys [5,6]. However, the price of rhenium, which is primarily consumed for the production of nickel base superalloys, has been substantially increasing for several years.…”
Section: Introductionmentioning
confidence: 99%